Pesquisa-ação para criação de sistemática de avaliação de riscos em responsabilidade civil em uma empresa de seguros - Moraes, Luciano Peloche (2016)
The insurance market in Brazil and in the world is passing through a considerable growth in its business. This growth is followed by an increasing level of claims that impact directly the results of the insurances companies that faces the challenge of seeing your profitability being consumed by the payment of indemnity to the insured customers. Some of the customers companies have bigger exposure to the Casualty risks, third part risks. One type of industry extremely exposed to those risks is the food industry. There are concepts and risk management techniques to face this trend of claims. This thesis present the development of a project to evaluate and manage risks in an insurance company, aiming to contribute to the quality improvement in the overwriting process of a casualty insurance policy, specifically to the food industry due to its high hazard. The insurance company mentioned has nine offices with nine overwriting teams in different countries, with different cultures, values, exigencies and litigiousness. Those important differences had a big impact in the speed of the implementation and, consequently, impacted also the obtained results. It has been evaluated quantitative results, as the number of inquiries to the engineering team, that present a 33% growth and also qualitative results, as the improvement of input data to the overwriting and engineering team. Another qualitative positive result was the overwriting of customers that was not even quoted in the past and finally the elimination of reinsurance to some customers. The last one will bring a positive result in a near future, by the end of the financial year. To summarize, it is presented the general overall evaluation process and opportunities of futures projects.